2022
DOI: 10.3390/atmos13122038
|View full text |Cite
|
Sign up to set email alerts
|

Soil Respiration and Organic Carbon Response to Biochar and Their Influencing Factors

Abstract: Biochar application is an important measure to regulate SOC. However, the effects of biochar application on soil respiration and SOC fraction of the saline soil have been scarcely investigated. Therefore, in this study, we monitored the annual SOC, nutrients, temperature, water content, and respiration rate under three maize-straw-derived biochar application doses (0, 15, and 30 t∙hm−2). Biochar enriched the soil in terms of fast-acting potassium and phosphorus, alkali-hydrolyzable N, NO3−-N, and NH4+-N to var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The very low initial organic carbon (1.32%) and macronutrient status of the acid soil studied mediated this reaction pathway such that a large proportion of the organic carbon built up following biochar application was channeled first into enhancing the soil macronutrient pool. A similar observation has been reported by Zhang et al 39 . The organic carbon and exchangeable acidity statuses of the soil after cowpea seedling harvesting are showing the need for further carbon build-up in the soil to achieve a situation where further increases in SOC content will account for a negative correlation with exchangeable acidity.…”
Section: Effects Of Biochar From Different Feedstock Combinations And...supporting
confidence: 91%
“…The very low initial organic carbon (1.32%) and macronutrient status of the acid soil studied mediated this reaction pathway such that a large proportion of the organic carbon built up following biochar application was channeled first into enhancing the soil macronutrient pool. A similar observation has been reported by Zhang et al 39 . The organic carbon and exchangeable acidity statuses of the soil after cowpea seedling harvesting are showing the need for further carbon build-up in the soil to achieve a situation where further increases in SOC content will account for a negative correlation with exchangeable acidity.…”
Section: Effects Of Biochar From Different Feedstock Combinations And...supporting
confidence: 91%
“…also apply to the biochar-supplemented microcosms: the lower apparent CO2 accumulation in the headspace with respect to the control microcosms might be due to the slight alkalinisation of the soil triggered by the biochar. Along this line, it is worth noting that recent studies have reported a decrease in soil respiration following biochar addition [51]. Methane, which is the other gaseous end-product of organic matter decomposition under anaerobic conditions, remained below the instrumental detection limit in all treatments during the whole experimental period.…”
Section: Biogas Productionmentioning
confidence: 62%
“…Similar considerations also apply to the biochar-supplemented microcosms: the lower apparent CO 2 accumulation in the headspace with respect to the control microcosms might be due to the slight alkalinisation of the soil triggered by the biochar. Along this line, it is worth noting that recent studies have reported a decrease in soil respiration following biochar addition [ 51 ].…”
Section: Resultsmentioning
confidence: 95%
“…In SOC and soil nutrients, straw biochar had the biggest effect value on SOC, but there was no significant difference with straw mulching on TN, AP, and AK. Straw biochar can significantly uplift the contents of available soil nutrients and SOC sequestration due to its physicochemical characteristics [72,73]. Compared with straw incorporation, straw mulching significantly increased TN, but there was no significant difference between straw incorporation and straw mulching in improving AP, AK, and SOC.…”
Section: Straw Formmentioning
confidence: 98%